Meissonier - Barbusse, Henri, 1873-1935; Roujon, Henry, 1853-1914; Cooper, Frederic Taber, 1864-1937 (Salt Lake City, UT : Project Gutenberg, 2013)
"Meissonier" by Henri Barbusse is a biography written in the early 20th century that explores the life and works of the French painter Jean-Louis-Ernest Meissonier (1815-1891). The book provides an in-depth look at Meissonier's artistic journey, emphasizing his dedication to realism and attention to detail, particularly in the realm of military painting. As a significant figure in the art world, Meissonier is often celebrated for his ability to capture the nuances of human expression and the atmosphere of historical moments. In this biography, Barbusse chronicles Meissonier's early years, his struggles to gain recognition, and his eventual rise to prominence through his meticulous and vibrant small-scale paintings. The narrative highlights key themes such as the artist's devotion to accuracy, the showcasing of human character, and his unique approach to depicting historical scenes without resorting to grandiose battle representations. Barbusse describes Meissonier's extensive research into costumes and his penchant for detail, which reflect his commitment to portraying a truthful representation of his subjects. The book ultimately celebrates Meissonier as a master of genre and military painting, capturing the essence of his artistic contributions to French art. (This is an automatically generated summary.)
Release date is 2013-07-03
E-text prepared by sp1nd, Matthew Wheaton, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Meissonier, Jean Louis Ernest, 1815-1891